Addressing the problem of sexual violence in South Africa : a philosophical analysis of equality and sexual difference in the constitution and the new sexual offences act - Coetzee, Azille Alta (Stellenbosch : Stellenbosch University, 2013)
Thesis (MA)--Stellenbosch University, 2013.